Selection of equipment for oil tank repair in northern conditions - V. N. Kuznetsova; I. S. Kuznetsov (Вестник СибАДИ, 2023)
Introduction. The oil industry is a key component of the economy of the Russian Federation. A large number of tanks are used to store oil, each of which needs timely repair. According to the results of some research, almost half of the accidents are caused by excess uneven settlement of the tank, which causes premature failure. To restore the serviceable and operable condition of the tanks, it is necessary to carry out repair work, the quality and efficiency of which depends on the repair equipment used. An urgent task is to justify the choice of equipment for the repair of tanks, in particular, steel tanks of a vertical type.Methods and materials. A review of the different types of tanks was carried out and showed that vertical steel tanks are the most widely used. One of the ways to eliminate the uneven settlement of the tank is to raise it with the help of jacks and form a new base with the elimination of the slope.Results. The repair process for a 10,000 m3 steel vertical tank was considered. The values of the mass of the tank were obtained when filling with liquid petroleum products at 1% of the maximum occupancy. The value of the load on one lifting device is obtained. The design of the device structure and the strength calculation in the Compass 3D program were completed.Сonclusions. The most efficient type of the lift from the existing ones was determined, and its design was modernized. The strength calculation showed that the hydraulic lift is efficient under the given conditions.